Mechanical properties of concrete containing recycled coarse aggregate at and after exposure to elevated temperatures - Shaikh, Faiz (International Federation of Prestressing, 2018)
This paper presents the effect of recycled coarse aggregate (RCA) of 50% and 100% by wt. on compressive strength and elastic modulus of concrete at elevated temperatures of 600 and 800 °C. The residual compressive strengths of above recycled aggregate concretes after exposure to elevated temperatures are also evaluated and compared to those measured during heating. The effect of polypropylene (PP) fibers on residual compressive strength and cracking behavior of above recycled aggregate concretes after exposure to elevated temperatures is also evaluated in this study. Results show that the loss of compressive strength of recycled aggregate concretes at 600 and 800 °C is slightly higher (about 10%) than its counterpart control concrete containing natural coarse aggregates. Concrete containing 100% RCA exhibited about 50% loss of its ambient temperature compressive strength at 800 °C, which is about 25% less in concrete containing 50% RCA. The residual compressive strength, which is measured after cooling of heated specimens, of both recycled aggregate concretes and control concrete is higher at both elevated temperatures. The measured elastic modulus of both recycled aggregate concretes show no significant reduction compared to their counterpart control concrete at both elevated temperatures. A strong correlation between elastic modulus and square root of compressive strength of recycled aggregate concretes is observed at elevated temperatures. The model proposed in Eurocode to predict the elevated temperature compressive strength and elastic modulus agrees well with the measured values for recycled aggregate concretes. The addition of PP fibers reduced the residual compressive strength of concrete containing 100% RCA at both temperatures with significant reduction at 800 °C. However, mixed results are obtained in the case of concrete containing 50% RCA. The cracking patterns of concrete containing RCA and those containing PP fibers also correlated well with the observed residual compressive strength results.